Optimization of mechanical and tribological properties of FCC CrCoNi multi-principal element alloy with Mo addition. (March 2018) - Miao, Junwei; Guo, Tieming; Ren, Junfang; Zhang, Aijun; Su, Bo; Meng, Junhu
Abstract: A new multi-principal element alloy system, CrCoNiMox, is designed by adding Mo in FCC CrCoNi alloy to improve the strength and wear resistance. The addition of Mo causes severe lattice distortion of the alloys and promotes the formation of intermetallic phases. With the increase of Mo content, the hardness and compressive yield strength of the CrCoNiMox alloys increase obviously from 244 HV and 518 MPa to 656 HV and 1973 MPa, respectively, whereas the plasticity decreases because the intermetallic compounds are hard but brittle. As a result of the competition between the solid solution strengthening of Mo and the embrittlement of the intermetallic compounds, the fracture toughness of the alloys firstly increases and then decreases with increasing Mo content. The wear resistance of the alloys is significantly increased with the Mo content and shows a slight increase when x exceeds 0.5, because the wear mechanism of the alloys is changed from abrasive wear to adhesive wear and brittle fracture gradually. This study provides a new insight for the design of high strength and wear resistant alloys for engineering applications. Highlights: A novel Mo-containing alloy system CrCoNiMox is designed and prepared by spark plasma sintering. The strength and wear resistance are improved due to the solid solution strengthening and the formation of intermetallics. The wear mechanism gradually changes from abrasive wear to adhesive wear and brittle fracture with increasing Mo content. The most excellent comprehensive properties of CrCoNiMox alloys is obtained in x = 0.5.